Effects of etching and adhesive applications on the bond strength between composite resin and glass-ionomer cements (Journal of Applied Oral Science, 2012)
OBJECTIVE: This study determined the effects of various surface treatment modalities on the bond strength of composite resins to glass-ionomer cements. MATERIAL AND METHODS: Conventional (KetacTM Molar Quick ApplicapTM) or resin-modified (PhotacTM Fil Quick AplicapTM) glass-ionomer cements were prepared. Two-step etch-rinse & bond adhesive (AdperTM Single Bond 2) or single-step self-etching adhesive (AdperTM PromptTM L-PopTM) was applied to the set cements. In the etch-rinse & bond group, the sample surfaces were pre-treated as follows: (1) no etching, (2) 15 s of etching with 35% phosphoric acid, (3) 30 s of etching, and (4) 60 s of etching. Following the placement of the composite resin (FiltekTM Z250), the bond strength was measured in a universal testing machine and the data obtained were analyzed with the two-way analysis of variance (ANOVA) followed by the Tukey's HSD post hoc analysis (p=0.05). Then, the fractured surfaces were examined by scanning electron microscopy. RESULTS: The bond strength of the composite resin to the conventional glass-ionomer cement was significantly lower than that to the resin-modified glass-ionomer cement (p